Effect of Cutting Parameter on Material Removal Rate and Surface Roughness in Deep Drilling Process - Abdullah, Mostafa A.; Abdulwahhab, Ahmed B.; Mohammed, Atheer R (Arab Journal for Sciences and Research Publishing, 2016)
In the curents study aimed to assess the effects of cutting conditions (spindle speed, feed rate, tool diameter) parameters as input impact on material removal rate (MRR) and surface roughness (Ra) as output of steel (AISI 1015). A number of drilling experiments were conducted using the L9 orthogonal array on conventional drilling machine with use feed rate (0.038,0.076,0.203) mm/rev and spindle speed (132,550,930) rpm and tool diameter (11,15,20) mm HSS twist drills under dry cutting conditions. Analysis of variance (ANOVA) was employed to determine the most significant control factors affecting on surface roughness and MRR. The result shown the tool diameter the important factor effect with (64.08%) and (76.12%) on MRR and surface roughness respectively.
Keywords: Taguchi; ANOVA; surface roughness; MRR; Tool diameter; Material Removal Rate